THE INFLUENCE OF DRILL PRACTICE ON VOLLEYBALL BOTTOM PASSING ABILITY IN CISUKADANA STATE ELEMENTARY SCHOOL - egisetiawan setiawan (Indonesian Journal of Education Teaching and Learning (IJETL), 2024)
The purpose of this research is to determine the effect of drill training on the lower passing ability of volleyball players at Cisukadana State Elementary School. The main problem in this research is that students' abilities in playing volleyball are still lacking, especially in the lower passing technique. This can be seen when the sport takes place, students have difficulty doing it. Apart from that, when the ball is bounced, students often don't pass, this is due to the lack of variety in learning volleyball, especially in passing, which causes the ability to pass less at Cisukadana State Elementary School. This research method uses the pre-experimental method with a one group pre test-post test design research design . The subjects in this research consisted of 15 grade IV students at Cisukadana State Elementary School. The data collection technique was carried out using pretest and posttest methods to obtain initial data using a volleyball underpassing skills test. Meanwhile, the data analysis technique uses descriptive statistical analysis and inferential analysis. Data is collected through observation, documentation and tests, data is analyzed quantitatively. The results of the research show that there is an effect of drill training on the bottom passing ability of volleyball players at Cisukadana State Elementary School. The findings of the sg hypothesis, (2-tailed) 0.000 are smaller than 0.05, meaning there is an effect of drill practice on the bottom passing ability of volleyball players at Cisukadana State Elementary School